Inorganic fertilizer in Uganda: Knowledge gaps, profitability, subsidy, and implications of a national policy - Bayite-Kasule, Stephen (International Food Policy Research Institute, 2009)
Agriculture is at the core of the livelihoods of most rural households in Uganda. It is a major engine for overall economic growth and possibly the single most important pathway out of poverty in the rural space. Although measures to enhance the rural farm economy are reflected in national policy through the Plan for Modernisation of Agriculture, tangible benefits, such as improved smallholder farm productivity, income growth, poverty reduction, and national food security, continue to elude the farm sector. Increasing the availability of inputs such as inorganic fertilizer and improved seed is critical to meeting the above policy objectives. The lack of functional and efficient agricultural inputs markets in Uganda is often highlighted among the major constraints to substantial agricultural growth in the country. Improved soil fertility management through increased levels of fertilizer use, increased use of available organic soil amendments, and improved farm management practices, together with the use of improved seed, can result in positive gains in farm productivity. This brief specifically addresses fertilizer use in Uganda.